2006
DOI: 10.5993/ajhb.30.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Change in Physical Exercise: A Test of Stage Discrimination and Nonlinearity

Abstract: Objectives: To investigate the utility of the protection motivation theory (PMT), social-cognitive theory (SCT) and transtheoretical model's (TTM) processes of change (POC) by (1) discriminating between TTM's stages with planned comparisons and (2) examining higher-ordered trends across stages. Methods: 1582 individuals were included in the analyses that tested severity, vulnerability, response-efficacy, self-efficacy, POC, pros and cons, social and environmental support. Results: The findings provide evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
(44 reference statements)
0
27
1
1
Order By: Relevance
“…The seasons add timing to the self-assessment. This timing is distinct from other staged approaches to behavior change [35][36][37][38][39] or any RET approaches. The influence of the season affects the type of intelligence one uses, the way a person goes about daily activities, and the resources available to that person.…”
Section: The Seasons Of Wellbeingmentioning
confidence: 94%
See 1 more Smart Citation
“…The seasons add timing to the self-assessment. This timing is distinct from other staged approaches to behavior change [35][36][37][38][39] or any RET approaches. The influence of the season affects the type of intelligence one uses, the way a person goes about daily activities, and the resources available to that person.…”
Section: The Seasons Of Wellbeingmentioning
confidence: 94%
“…A broad range of methodologies and applications can utilize ROH. In this way, ROH may contribute to the literature on the set-point theory of well-being, 31 positive psychology, 32,33 the field of behavior change [34][35][36][37][38][39][40] and the more-allopathic approaches to health and medicine, herein termed Restorative Therapeutics (RET).…”
mentioning
confidence: 98%
“…West (2005) has summarised this critique and has concluded that the TTM needs to be abandoned. However, more recent empirical evidence has emerged in favor of the TTM, suggesting that the notion of stages of behavior change is meaningful and has pragmatic value (Lippke, Nigg, & Maddock, 2007; Lippke & Plotnikoff, 2006; Velicer et al, 2006; Velicer, Redding, Anatchkova, Fava, & Prochaska, in press; Velicer, Redding, Sun, & Prochaska, 2007; Velicer, Friedman, Fava, Gulliver, Keller, Sun, Ramelson, & Prochaska, in press).…”
Section: Continuum Models Versus Stage Models Of Health Behavior Changementioning
confidence: 99%
“…Finally, in a study assessing the utility of the PMT, Social Cognitive Theory and stage classification (Lippke & Plotnikoff, 2006), severity, vulnerability, response efficacy and self-efficacy were significantly different between individuals who were not considering change versus those contemplating change. The researchers found that those individuals in precontemplation perceived significantly fewer pros and insignificantly more cons than did individuals in other stages, with the highest scores in precontemplators and lowest in maintenance.…”
Section: Age and Gender As Moderators Of Threat Cognitionsmentioning
confidence: 98%